2016
DOI: 10.1016/j.bonr.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Intraskeletal variation in human cortical osteocyte lacunar density: Implications for bone quality assessment

Abstract: Osteocytes and their lacunocanalicular network have been identified as the regulator of bone quality and function by exerting extensive influence over metabolic processes, mechanical adaptation, and mineral homeostasis. Recent research has shown that osteocyte apoptosis leads to a decrease in bone quality and increase in bone fragility mediated through its effects on remodeling. The purpose of this study is to investigate variation in cortical bone osteocyte lacunar density with respect to major factors includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 93 publications
3
23
0
Order By: Relevance
“…BMD and T 1 showed significant increases from the inner layer towards the outer layer ( p < 0.01). Such results were in agreement with the multiple previous studies that have shown lower intracortical porosity and pore size on the periosteal side compared with the endosteal side, using a variety of methods including high‐resolution microscopy, histology, and high‐resolution quantitative CT …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BMD and T 1 showed significant increases from the inner layer towards the outer layer ( p < 0.01). Such results were in agreement with the multiple previous studies that have shown lower intracortical porosity and pore size on the periosteal side compared with the endosteal side, using a variety of methods including high‐resolution microscopy, histology, and high‐resolution quantitative CT …”
Section: Discussionsupporting
confidence: 92%
“…BMD and T 1 showed significant increases from the inner layer towards the outer layer (p < 0.01). Such results were in agreement with the multiple previous studies that have shown lower intracortical porosity and pore size on the periosteal side compared with the endosteal side, using a variety of methods including high-resolution microscopy, histology, and high-resolution quantitative CT. [42][43][44][45] The results of this study suggested that MMF from UTE-MT modeling is a useful and promising surrogate for assessing human intracortical porosity and BMD in particular for specimens from donors with no known bone disease. This MRI based technique is non-invasive, x-ray free, and importantly translatable to in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, osteoblast apoptosis triggered by sex steroid withdrawal may result in reduced osteocyte densities (i.e., fewer cells to differentiate into mature osteocytes) after menopause (Bradford, Gerace, Roland, & Chrzan, ). While the women in our study demonstrate greater lacunar abundance across the entire adult lifespan compared to men, the lack of significant relationships with age supports a paradigm shift away from estrogen‐centric effects on this aspect of bone quality (Hunter & Agnew, ; Manolagas & Parfitt, ). In agreement, Qiu et al (2002b) also did not find a relationship between osteocyte lacunar density (Ot.Lc.Dn) and the menopause transition.…”
Section: Discussionmentioning
confidence: 45%
“…Early work suggested that the ratio of Ct.Po to bone area remains relatively constant across the adult lifespan in the human rib (Frost, 1963); however, this assertion has been contested. Newer research has not identified any sex‐based differences, but studies demonstrate a linear increase in Ct.Po with age (Dominguez & Agnew, ; Hunter & Agnew, ). This relationship has been described to varying degrees in men and women at other anatomical locations (Bach‐Gansmo et al, ; Bousson et al, ; Brockstedt, Kassem, Eriksen, Mosekilde, & Melsen, ; Burghardt et al, ; Feik, Thomas, & Clement, ; Hansen et al, ; Kazakia et al, ; Macdonald et al, ; Vilayphiou, Boutroy, Sornay‐Rendu, Rietbergen, & Chapurlat, ), but direct comparisons to our results may not be appropriate given differences in mechanical loading between skeletal elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation